(untitled) - Aghion, Philippe (Cambridge,New York, 1998)
Two of the world's leading economists, Philippe Aghion (a theorist) and Jeffrey Williamson (an economic historian), jointly question the conventional wisdom on inequality and growth, and address its inability to explain recent economic experience. Aghion assesses the effects of inequality on growth, and asks whether inequality matters: is excessive inequality bad for growth, and is it possible to reconcile aggregate findings with microeconomic theories of incentives? Jeffrey Williamson then discusses the Kuznets hypothesis, and focuses on the causes of wage and income inequality in developed economies
Keywords: Economic development,Income distribution,Phát triển kinh tế